2016
DOI: 10.1039/c5cc09041e
|View full text |Cite
|
Sign up to set email alerts
|

Making C–H bonds with CO2: production of formate by molecular electrocatalysts

Abstract: Molecular approaches to the electrocatalytic reduction of CO2 to formate are varied and versatile in their methods. We discuss recent efforts to catalyse this reaction including significant progress made in the last 5 years. This Feature Article begins with a survey of molecular electrocatalysts that produce CO or H2, but have been observed under certain conditions to afford some formate. These examples are included because they provide valuable mechanistic insight for design of catalysts that produce hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 134 publications
(58 reference statements)
0
77
0
1
Order By: Relevance
“…Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 . Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 . Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In light of previous reports, [10,14,36,37] experimental observations and standard electron counting rules lead us to propose a photocatalytic mechanismf or HCO 2 Hp roduction from CO 2 by using complexes 1 + + Cl À and 2 + + Cl À (Scheme 2a nd FigureS8). [36,37] In addition, the fact that we did not observe formation of CO as ap roduct also mitigated against formation of aC O 2 adduct with Ru 0 .T hus, protonation of this lone electron pair of Ru 0 yields the hydridec omplex, RuH.T he insertiono fC O 2 into the RuÀHc omplex yields the metallacarboxylic acid species RuCOOH,w hich through reduction releases formate and generatest he Ru I complex Ru + + .T he catalytic cycle closes with return to Ru 0 by reduction from PS À . Entry into the catalytic cycle comes from the reduction of A ( Figure S10), which during optimization, spontaneously dissociated aC l À anion to yield ad istorted square pyramidal complex labeled Ru 0 .V isualization of the HOMO of this complex shows that the electron density is localized in ad z 2 -type orbital with some contributions from the CO ligands ( Figures S11a nd S12).…”
mentioning
confidence: 72%
“…Carbon dioxide holds immense promise as a sustainable feedstock for the synthesis of high energy density fuels . Research has revealed that electrocatalytic reduction of carbon dioxide to carbon oxide, formic acid, or other high added‐value products can provide a promising strategy for reducing greenhouse gas and solving energy issues . Development of catalysts with high selectivity, efficiency, and stability for converting CO 2 is still very challenging.…”
Section: Introductionmentioning
confidence: 99%